PENGARUH PANJANG HARI TERHADAP PRODUKSI BIJI ALFALFA (Medicago sativa L) DI SEMARANG - Renan Subantoro; Lutfi Aris Sasongko; Rossi Prabowo (MEDIAGRO, 2014)
Six different long lighting will have an influence on the growth and yield quality of alfalfa seed. The objective of this research is knowing long lighting optimum which result optimum growth and yield quality of alfalfa seed.  The experiment was conducted using a completely randomized design (CRD) with single experiment on June until December 2013 in the Green House facility that owned by Faculty of Agriculture Wahid Hasyim University in Semarang. Data observed were analyzed by analysis of variance with a completely randomized design, and followed by Duncan's multiple range test at the level of 5%. The lighting treatment on alfalfa at night were not lighting as control, 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours. The result of the study showed that all treatment were tried on alfalfa crops variety of WL 625 HQ didn’t produce flowers and seed.   Keywords: Alfalfa, growth, long day plant, long  lighting, quality of alfalfa seed yield.